2017
DOI: 10.12968/ajmw.2017.11.2.67
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to intrapartum stillbirth: a criteria-based audit to support midwifery practice in Zambia

Abstract: Background: Stillbirth is a poor pregnancy outcome and one that is common worldwide. It mostly occurs during the intrapartum period, which accounts for more than 50% of cases. Estimates suggest that 55% of stillbirths occur in low-to middle-income countries (Lawn et al, 2011). Objective: To establish factors contributing to intrapartum stillbirth in Mansa General Hospital, Lupala Province, Zambia. Methods: In this retrospective audit, the files of 115 women were purposively reviewed in an initial baseline clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The included studies had one or more of the following aims when conducting a stillbirth review: to prevent stillbirth, to improve all aspects of care by making adequate and informed recommendation guided by clear local/national/international criteria or practices 3 , 15 , 17 , 25 , 36 , 39 , 43 , 46 , 51 , 52 , 55 , 56 , 57 , 64 , 65 , 69 , 73 , 75 ; to analyse cause/s of stillbirth and/or any suboptimal care during the pregnancy 3 , 10 , 11 , 15 , 16 , 19 , 20 , 21 , 22 , 23 , 24 , 26 , 28 , 29 , 30 , 31 , 32 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 45 , 47 , 50 , 53 , 54 , 58 , 59 , 61 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 77 ; to evaluate the current review process or tool implemented and what the facilitators or barriers were…”
Section: Resultsmentioning
confidence: 99%
“…The included studies had one or more of the following aims when conducting a stillbirth review: to prevent stillbirth, to improve all aspects of care by making adequate and informed recommendation guided by clear local/national/international criteria or practices 3 , 15 , 17 , 25 , 36 , 39 , 43 , 46 , 51 , 52 , 55 , 56 , 57 , 64 , 65 , 69 , 73 , 75 ; to analyse cause/s of stillbirth and/or any suboptimal care during the pregnancy 3 , 10 , 11 , 15 , 16 , 19 , 20 , 21 , 22 , 23 , 24 , 26 , 28 , 29 , 30 , 31 , 32 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 45 , 47 , 50 , 53 , 54 , 58 , 59 , 61 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 77 ; to evaluate the current review process or tool implemented and what the facilitators or barriers were…”
Section: Resultsmentioning
confidence: 99%
“…The second three studies used a confidential inquiry approach 19 or external researchers 20 or external and internal auditors. 21 These external multidisciplinary teams were not involved in the care of patients; they audited the cases and gave feedback to facility staff to implement recommendations.…”
Section: Resultsmentioning
confidence: 99%
“…No study reported newborn morbidity outcomes. One study 21 reported a reduction in the incidence of maternal obstetric complications such as obstructed labour and antepartum haemorrhage, which contributes to stillbirths, following the implementation of a fresh stillbirth audit using standards as a benchmark ( table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations